Intracellular and Intercellular Aspects of Macrophage Immunometabolism in Atherosclerosis - Tabas, Ira; Bornfeldt, Karin E (Circulation research, 2020)
Macrophage immunometabolism, the changes in intracellular metabolic pathways that alter the function of these highly plastic cells, has been the subject of intense interest in the past few years, in part because macrophage immunometabolism plays important roles in atherosclerosis and other inflammatory diseases. In this review article, part of the , we introduce the concepts of (1) intracellular immunometabolism-the canonical pathways of intrinsic cell activation leading to changes in intracellular metabolism, which in turn alter cellular function; and (2) intercellular immunometabolism-conditions in which intermediates of cellular metabolism are transferred from one cell to another, thereby altering the function of the recipient cell. The recent discovery that the metabolite cargo of dead and dying cells ingested through efferocytosis by macrophages can alter metabolic pathways and downstream function of the efferocyte is markedly changing the way we think about macrophage immunometabolism. Metabolic transitions of macrophages contribute to their functions in all stages of atherosclerosis, from lesion initiation to formation of advanced lesions characterized by necrotic cores, to lesion regression following aggressive lipid lowering. This review article discusses recent advances in our understanding of these different aspects of macrophage immunometabolism in atherosclerosis. With the increasing understanding of the roles of macrophage immunometabolism in atherosclerosis, new exciting concepts and potential targets for intervention are emerging.